Acute onset of focal seizures, psychiatric features and confusion: a case of autoimmune encephalitis? - Al-Diwani, A; Butterworth, R; Nibber, A; Lang, B; Vincent, A; Irani, SR (2012)
An elderly woman presented with disorganised thinking, unusual behaviour and clustered episodes of speech arrest accompanied by right-sided face and arm twitching. The following investigations were normal: interictal electroencephalography, brain MRI, cerebrospinal fluid viral PCR and cell count and voltage-gated potassium channel-complex, N-methyl-d-aspartate receptor, gamma-aminobutyric acid (B) receptor, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor, glycine receptor, glutamic acid decarboxylase and paraneoplastic antibodies. The syndrome showed partial spontaneous resolution but 1 year later, typical postencephalopathic features persisted including disinhibition and alteration of sleep-wake cycle. The most likely clinical diagnosis was autoimmune encephalitis and the broader differential diagnoses are discussed within the article. This case demonstrates the need to be aware of this under-recognised and potentially treatable entity.